A Comprehensive Analysis of Short Specific Tissue (SST) Proteins, a New Group of Proteins from PF10950 That May Give Rise to Cyclopeptide Alkaloids - Lucía Albornos; Paula Iriondo; Silvia Rodríguez-Marcos; Patricia Farelo; Guillermo Sobrino-Mengual; Luz María Muñoz-Centeno; Ignacio Martín; Berta Dopico (Plants)
Proteins of the PF10950 family feature the DUF2775 domain of unknown function. The most studied are specific tissue (ST) proteins with tandem repeats, which are putative precursors of cyclopeptide alkaloids. Here, we study uncharacterised short ST (SST) proteins with the DUFF2775 domain by analysing 194 sequences from 120 species of 39 taxonomic families in silico. SST proteins have a signal peptide and their size and several other characteristics depend on their individual taxonomic family. Sequence analyses revealed that SST proteins contain two well-conserved regions, one resembling the ST repeat, which could constitute the core of cyclopeptide alkaloids. We studied the unique SST1 gene of Arabidopsis thaliana, which is adjacent to and co-expressed with a gene encoding a protein with a BURP domain, associated with cyclopeptide production. The empirical analysis indicated that the SST1 promoter is mainly activated in the roots, where most of the transcripts accumulate, and that the SST1 protein accumulates in the root vascular cambium. At the cellular level, SST fused to GFP appears in vesicles that co-localise with the endoplasmic reticulum and the vacuole. Thus, SSTs are a new type of PF10950 protein found in core eudicots with two conserved regions that could be involved in root biology.